Ieee Infocom 2004
DOI: 10.1109/infcom.2004.1357026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating location predictors with extensive Wi-Fi mobility data

Abstract: Abstract-Location is an important feature for many applications, and wireless networks can better serve their clients by anticipating client mobility. As a result, many location predictors have been proposed in the literature, though few have been evaluated with empirical evidence. This paper reports on the results of the first extensive empirical evaluation of location predictors, using a two-year trace of the mobility patterns of over 6,000 users on Dartmouth's campus-wide Wi-Fi wireless network.We implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…Fortunately, large residence times before transiting into an OFF state is a dominant feature in the collected data rendering 30-minute inaccuracy insignificant. More details on the data collection method and the network can be found in [6,13].…”
Section: System Model Assumptions and Methodologymentioning
confidence: 99%
“…Fortunately, large residence times before transiting into an OFF state is a dominant feature in the collected data rendering 30-minute inaccuracy insignificant. More details on the data collection method and the network can be found in [6,13].…”
Section: System Model Assumptions and Methodologymentioning
confidence: 99%
“…Previous work [9] has shown that the trace length for different users shows very wide variability, with a median of 494 and a maximum of 188,479 APs visited. However observe that, on average, users visit only a few distinct APs per day that they are active; see Fig.…”
Section: Locality and Hierarchymentioning
confidence: 99%
“…A limitation of the data is that the OFF state is not always accurately captured. Further details of the data and collection process are described in [8,9].…”
Section: Empirical Datamentioning
confidence: 99%
“…It is trained by constructing a transition matrix based on history trajectories, which indicates the transition probability between locations. The next location will be inferred depending on the current status and the transition matrix [13]. Pattern-based techniques aim to mine the mobility patterns existing in history trajectories by utilizing association rule methods.…”
Section: Introductionmentioning
confidence: 99%